2006
DOI: 10.1097/01.pai.0000155795.41654.b1
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/neu in Breast Cancer

Abstract: HER-2/neu is a protooncogene frequently overexpressed in breast cancer. Fluorescence in situ hybridization (FISH) is a technique targeting the gene amplification, while immunohisto-chemistry detects the protein expression. Usually both are applied to paraffin-embedded tissue. The authors studied HER-2 by FISH and immunohistochemistry (HercepTest) in 81 breast carcinomas. The results showed an overall concordance (correlation coefficient 0.64). In all cases with HercepTest score 0 and 1+, nonamplification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Of the 54 cases with 2+ staining, only 26 (48%) showed HER2 gene amplification by FISH [156]. Several other studies have also shown absence of gene amplification in subset of cases which were scored 2+ by IHC [147, 149, 153, 154, 157, 158]. Hence, a combined approach with IHC and FISH analysis was recommended for accurate HER2 testing particularly for cases with moderate staining with IHC [137, 148, 149, 152, 157].…”
Section: Her2 Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 54 cases with 2+ staining, only 26 (48%) showed HER2 gene amplification by FISH [156]. Several other studies have also shown absence of gene amplification in subset of cases which were scored 2+ by IHC [147, 149, 153, 154, 157, 158]. Hence, a combined approach with IHC and FISH analysis was recommended for accurate HER2 testing particularly for cases with moderate staining with IHC [137, 148, 149, 152, 157].…”
Section: Her2 Testingmentioning
confidence: 99%
“…Several studies have identified a subset of false positive breast cancers that are IHC 3+ and negative by FISH ranging from 3% to 22% of all positive cases [146, 148, 153, 156158, 160]. These inconsistencies may be due to several causes including variability in tissue fixation and processing, intratumoral heterogeneity, and polysomy of chromosome 17 [166, 167].…”
Section: Current Issues With Her2 Testingmentioning
confidence: 99%
“…Tagged photocleavable linkers can be chemically attached to different classes of probes such as DNA, cDNA, single stranded cRNA, or antibody probes. They can then be used in conjunction with classical tissue-specific molecular targeting using either hybridization methods for oligonucleotides with In Situ Hybridization (ISH) or paratope-epitope interaction with immuhistochemistry (IHC) approach for antibody probes 1 (A) Schematic representation of the concept of MALDI imaging of mRNA using tagged oligonucleotide probes for detection by photocleavage.…”
Section: Introductionmentioning
confidence: 99%